Xây dựng hàm đo trên đại số gia tử và ứng dụng trong lập luận ngôn ngữ - Khang, Trần Đình (Journal of Computer Science and Cybernetics, 2016)
This paper gives the conception of a measure function on hedge algebras, which is useful to implementation of linguistic reasoning in application of decision support systems to social economic and management problems.